Optimizing the Navitaire System at AirAsia Malang Branch: Enhancing Service Completeness and Customer Satisfaction - Sunarto, Billy Tian; Islamiyah, Mufidatul (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This research paper aims to optimize the Navitaire system at AirAsia Malang to address the gap in customer preferences for direct bookings compared to third-party platforms. Understanding this issue is significant for enhancing customer satisfaction and service completeness in the aviation sector. Method: The study employs a qualitative research design, utilizing direct observation, staff interviews, and document analysis to assess the current state of the Navitaire system and identify areas for improvement. Practical Applications: The findings suggest that implementing targeted strategies, such as staff training and IT infrastructure enhancements, can improve service offerings, leading to better resource management and increased customer satisfaction. Conclusion: The study concludes that optimizing the Navitaire system significantly enhances operational efficiency and customer preference for direct bookings at the Malang branch, contributing valuable insights to the field of aviation service management.